2020
DOI: 10.1021/acsaem.0c02053
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Imaging of Pore Formation in Li Metal Solid-State Batteries Aided by Machine Learning

Abstract: High-rate capable, reversible lithium metal anodes are necessary for next generation energy storage systems. In situ tomography of Li|LLZO|Li cells is carried out to track morphological transformations in Li metal electrodes. Machine learning enables tracking the lithium metal morphology during galvanostatic cycling. Nonuniform lithium electrode kinetics are observed at both electrodes during cycling. Hot spots in lithium metal are correlated with microstructural anisotropy in LLZO. Mesoscale modeling reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 32 publications
0
67
0
1
Order By: Relevance
“…The green phase is the identified lithium metal while the blue phase is the identified pore/void phases. Reproduced with permission from (Dixit et al, 2020). Copyright 2020 American Chemical Society.…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The green phase is the identified lithium metal while the blue phase is the identified pore/void phases. Reproduced with permission from (Dixit et al, 2020). Copyright 2020 American Chemical Society.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…To assist the interpretation of in-situ Li metal morphological transformations during galvanostatic cycling in Li|LLZO|Li cells, Dixit et al trained a convolution ANN and observed non-uniform Li electrode kinetics at both electrodes during cycling (Figure 11). The hot spots in Li metal are correlated with microstructural anisotropy in LLZO (Dixit et al, 2020). Advanced visualization combined with electrochemistry represents an important strategy to resolve non-equilibrium effects that limit rate capabilities of SSBs.…”
Section: Interfaces and Coatingsmentioning
confidence: 99%
“…Interfacial kinetics heterogeneity at the Li metal solid electrolyte interface initiates several degradation pathways including filament formation limiting the stability and performance of solid-state batteries. In addition to growth of filaments, high rate electrodissolution from the Li metal can lead to formation of pores that can cause onset of failure [75]. A direct evidence of this was obtained from X-ray tomography measurements of Li | LLZO | Li symmetric cells (Figure 5c).…”
Section: Anode Materials and Designs For Ssbmentioning
confidence: 94%
“…(c) Porosity for two lithium metal electrodes as a function of cycling steps obtained from X-ray tomography measurements and machine learning segmentation. Reprinted with permission from[75]. (d) Silicon | LPS | Li cell cycling behavior.…”
mentioning
confidence: 99%
“…An example of this from Dixit et al contrasted segmentation results from the commonly used Otsu thresholding (binary) algorithm and a convolutional neural network on reconstructions from X-ray tomography on a symmetric Li|LLZO (Li 7 La 3 Zr 2 O 12 )|Li cell. [120] The neural network architecture was trained on 800 images starting with manual labeling and was crucial in being able to distinguish Li metal from surrounding pores that form during cycling. The resulting segmentation employing the neural network also allows for quantitative analysis of porosity during plating and stripping.…”
Section: Quantitative Imaging-based Techniquesmentioning
confidence: 99%